Nalar Fatwa-Fatwa ‘Umar Ibn al-Khattab: Menemukan Fleksibilitas Hukum Berbasis Tekstualisme - Tarmizi (Universitas Islam DDI AG.H. Abdurrahman Ambo Dalle, 2025)
This study examines the fatwas of 'Umar ibn Khattab and argues that they are firmly rooted in a deep textual-based understanding of the Qur'anic text. This study uses the library research method, analyzing 'Umar's fatwas and relevant literature to see the reasoning of his fatwas. A narrative-philosophical analysis is used to discuss how 'Umar's fatwas are firmly rooted in Islamic legal theories (ushul al-fiqh) This study concludes that 'Umar's fatwas are in line with the vision of the Qur'an and hadith. At first glance, 'Umar's fatwas do not seem to be in accordance with the text, but if traced further using the Ushul al-Fiqh approach, all the fatwas issued by 'Umar are in line with the agreed rules, namely using tahqiq al-manat in the fatwa on the elimination of the muallaf zakat portion, 'am and khas in the fatwa on the elimination of the law of hand cutting for thieves in times of famine, and dalalah al-nash and sad al-zari'ah in the fatwa on the law of qisas for people who conspire to commit murder. The results of 'Umar's fatwa are not only in line with the orientation of maslahah, but his vision is affirmed by the text of the Qur'an and hadith using textual reasoning Ushul al-Fiqh